Corporate Governance and Corporate Tax Avoidance: an Interactive Effects (Evidence from Indonesia Capital Market) - Agoestina Mappadang (University of Merdeka Malang, 2021)
This study shows that the phenomenon arising from low governance practices is identified as one of the causes of the global financial crisis and corporate financial scandals that have an effect on the increase of tax avoidance. In addition, research in Indonesia that examines tax avoidance information by taking into account corporate governance mechanisms is still less consistent and is such a new perspective that it becomes a main consideration for this study. Likewise, the calculation using the Avoidance Tax Rate proxy developed in this study was conducted to test how much tax avoidance has been done by companies. The population for this study was taken from the manufacturing industries listed on the Indonesia Stock Exchange from 2015-2019 assumed to have conducted tax avoidance. The total samples of 87 companies were selected by following a purposive sampling procedure. The statistical analysis using multiple regression shows that the board of commissioners had a significant negative effect on tax avoidance; while, Independent commissioners had a significantly negative effect on tax avoidance and institutional ownership on tax avoidance. This study indicates that the interactive effect of corporate governance and tax avoidance is the better and optimal corporate governance as a control mechanism and the balancing power. The lower the company does tax avoidance, the lower corporate governance mechanism will make it easier for companies to take tax avoidance actions.DOI: https://doi.org/10.26905/jkdp.v25i1.5043